Beyond the hashtag: describing and understanding the full impact of the #BJSConnect tweet chat May 2019. Issue 2 (13th December 2020) - Mackenzie, G; Grossman, R; Mayol, J
Abstract: Background: Twitter engagement between surgeons provides opportunities for international discussion of research and clinical practice. Understanding how surgical tweet chats work is important at a time when increasing reliance is being placed on virtual engagement because of the COVID-19 pandemic. Methods: Individual tweets from the May 2019 #BJSConnect tweet chat were extracted using NodeXL, complemented by Twitter searches in an internet browser to identify responses that had not used the hashtag. Aggregate estimates of tweet views were obtained from a third-party social media tool (Twitonomy) and compared with official Twitter Analytics measurements. Results: In total 37 Twitter accounts posted 248 tweets or replies relating to the tweet chat. A further 110 accounts disseminated the tweets via retweeting. Only 58.5 per cent of these tweets and 35 per cent of the tweeters were identified through a search for the #BJSConnect hashtag. The rest were identified by searching for replies (61), quoting tweets (20), and posts by @BJSurgery that used the hashtag but did not appear in the Twitter search (22). Studying all tweets revealed complex branching discussions that went beyond the discussed paper's findings. Third-party estimates of potential reach of the tweet chat were greatly exaggerated. Conclusion: Understanding the extent of the discussion generated by the #BJSConnect tweet chat required looking beyond the hashtag to identify replies and other responses, which was time-consuming. Estimates of reach using a third-party tool were unreliable. Abstract : This analysis of the #BJSConnect tweet chat in May 2019 looks beyond the hashtag to identify the extent of dialogue between contributors. Adding in tweets and replies that did not use the hashtag almost tripled the number of contributors of original content, and identified over 100 additional tweets, many of which added to the understanding of the research paper being discussed. The findings illustrate the complexity of understanding social media dialogue and are particularly relevant, as much of our scientific and clinical discussion has moved online because of the Covid-19 pandemic. #beyond the hasht tag